Unsteady Flow of a Dusty Viscous Fluid Between Two Wavy Walls - Verma, P. D.; Sarangi, K. C. (Defence Science Journal, 2014)
To understand the abnormal flow conditions, an analytical solution for the velocity of the fluid and the dust particles are obtained for the unsteady flow of a dusty viscous fluid under the influence of a constant pressure gradient, betwwen two plates with roughness along their length, whose equations are taken in the formof fourier series the assumption that E, the coefficient of roughness is small. The velocity profiles have been determined to the first order E.